Speech Acts of Condolences in English and Indonesian: A Cross-Cultural Study - Frisca Putrisia; Haniifatun Ubaidillah; Valerie Raissa; Azzahrine Rahmania; Wirdatul Khasanah (Universitas Negeri Surabaya, 2025)
Using Searle’s (1979) Speech Acts framework and Elwood’s (2004) Semantic formulas, this study investigates how condolences are expressed differently in four grief-related scenarios by both British and Indonesian. The data were collected through a Discourse Completion task (DCT) completed by 10 Indonesian participants and 10 British participants. The finding shows that while Indonesian participants rely most on religious expression and future-oriented remarks, British predominantly employ expressions of sympathy and offer assistance. Both groups demonstrate similarities in using personal questions and empathetic comments. However, the variation occurs based on closeness of the relationship. This result highlights the cultural sensitivity of condolence expressions and the importance of understanding cross cultural communicative strategies in emotionally charged interactions.